2023
DOI: 10.1177/11795484231152304
|View full text |Cite
|
Sign up to set email alerts
|

Serum Krebs von den Lungen-6 for Predicting the Severity of COVID-19: A Systematic Review, Meta-Analysis, and Trial Sequence Analysis

Abstract: OBJECTIVE This systematic review and meta-analysis aimed to find the association between serum Krebs von den Lungen-6 (KL-6) and the severity of Coronavirus disease 2019 (COVID-19) infection. DATA SOURCES Databases of Embase, PubMed, Web of Science, Science Direct, and Google Scholar were searched for studies reporting KL-6 levels in COVID-19 patients, published between January 2020 and September 30 2022. DATA SYNTHESIS For comparison between the groups, standard mean difference (SMD) and 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Elevated serum levels of KL-6 have been identified as a biomarker for alveolar epithelial proliferation and injury in various respiratory conditions (10), including acute respiratory distress syndrome (11), hypersensitivity pneumonia (12), idiopathic interstitial pneumonia (13), pulmonary sarcoidosis (14), coronavirus disease 2019 (COVID-19) (15), and CTD-ILD (16). Furthermore, several studies have indicated the potential predictive value of serum KL-6 in determining the prognosis of individuals with severe lung conditions, including idiopathic pulmonary fibrosis (17) and COVID-19 (18). Nevertheless, research examining the correlation between serum KL-6 levels and mortality risk in patients with CTD-ILD has yielded conflicting results (19).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum levels of KL-6 have been identified as a biomarker for alveolar epithelial proliferation and injury in various respiratory conditions (10), including acute respiratory distress syndrome (11), hypersensitivity pneumonia (12), idiopathic interstitial pneumonia (13), pulmonary sarcoidosis (14), coronavirus disease 2019 (COVID-19) (15), and CTD-ILD (16). Furthermore, several studies have indicated the potential predictive value of serum KL-6 in determining the prognosis of individuals with severe lung conditions, including idiopathic pulmonary fibrosis (17) and COVID-19 (18). Nevertheless, research examining the correlation between serum KL-6 levels and mortality risk in patients with CTD-ILD has yielded conflicting results (19).…”
Section: Introductionmentioning
confidence: 99%